Clinical Application Prospect of Human Synovial Tissue Stem Cells from Osteoarthritis Grade IV Patients in Cartilage Regeneration - Rahmadian, Rizki; Adly, Marlina; Dilogo, Ismail Hadisoebroto; Revilla, Gusti (Open Access Macedonian Journal of Medical Sciences, 2021)
Osteoarthritis (OA) is a joint problem that continues to increase in prevalence as life expectancy increases. OA can affect any joint, especially those that support body weight such as the knee and hip joint. Although both primary and secondary OA have the same clinical symptoms, it can be caused by different etiologies. OA is no longer considered a degenerative disease, although age is still a major factor. Various attempts have been made to regenerate joint cartilage damaged by OA. The use of stem cells in OA therapy is a very promising opportunity. Stem cells are undifferentiated biological cells and are multipotent to differentiate into specific cells. In principle, local stem cells are the best source of stem cells to regenerate the surrounding tissue. The synovial membrane is a tissue in the joint that can regenerate. After synovectomy surgery, repair, and growth of synovial tissue occur rapidly. Synovial tissue as a source of stem cells only provides a limited amount. One source of synovial tissue that can be used is tissue taken from the total knee replacement process in grade 4 OA patients. However, it is necessary to prove the potential of synovial tissue stem cells originating from old-age donors.